2021
DOI: 10.1002/lio2.622
|View full text |Cite
|
Sign up to set email alerts
|

Tympanostomies and tonsillar surgery in children during the COVID‐19 pandemic in Finland

Abstract: Objective To assess the impact of social restrictions due to COVID‐19 on the number of tympanostomies and tonsillar surgeries in children. Methods Incidences were calculated per 100 000 children for tonsillar surgery and tympanostomies in 2020 and compared to the mean incidence of referral years 2017 to 2019 by incidence rate ratios (IRR) with 95% confidence intervals (CIs). Median waiting times were also compared. Results Before the lockdown, tonsillar surgery incidence was 33.4/100000 (IRR 1.14, CI 0.76‐1.71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…Gatherings were limited to two persons, and avoiding traveling was recommended. The various measurements resulted not only in a decreased number of COVID-cases but also in a reduction in the number of airway infections in general [20] and particularly in children [21]. This is strongly confirmed by the findings of our study revealing a significantly reduced number doctor contacts with antibiotic prescriptions, particularly in the second quarter (Table 3; Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Gatherings were limited to two persons, and avoiding traveling was recommended. The various measurements resulted not only in a decreased number of COVID-cases but also in a reduction in the number of airway infections in general [20] and particularly in children [21]. This is strongly confirmed by the findings of our study revealing a significantly reduced number doctor contacts with antibiotic prescriptions, particularly in the second quarter (Table 3; Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, since there was no compensatory increase in this indication for surgery there must have been a spontaneous resolution taken place. Haapanen et al reported a decrease in the total number of tonsil surgery in 2020 by 37.3% based on rather small pediatric patient population (n = 568 vs. 106.526 of our study) in Finland [21]. The findings compare well to our study (− 34.0%) concerning elective surgery but our update for the first 5 months of the year 2021 revealed a stronger effect (− 54.5%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[15][16][17][18][19] Studies in the USA and Finland have also found lower rates of bilateral myringotomy and tube insertions during the Covid-19 pandemic. 20,21 These findings support our hypothesis that the reduced rate of bilateral myringotomy and tube insertions in New Brunswick during the pandemic was due to decreased URTI transmission.…”
Section: Discussionsupporting
confidence: 71%
“…Certainly, this study has some limitations. First, our cohort recruitment was badly interrupted due to the COVID-19 world pandemic that reduced our sample size due to a rapid and surprising large reduction of acute otitis media incidence 31,32 . In particular, the azithromycin treatment group was too small.…”
Section: Discussionmentioning
confidence: 99%